2011
DOI: 10.3748/wjg.v17.i47.5184
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation improves sustained virologic response in chronic hepatitis C (genotype 1)-naïve patients

Abstract: Adding vitamin D to conventional Peg-α-2b/ribavirin therapy for treatment-naïve patients with chronic HCV genotype 1 infection significantly improves the viral response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
3
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(177 citation statements)
references
References 26 publications
4
164
3
6
Order By: Relevance
“…Further, vitamin D deficiency was associated with several immunemediated diseases and increased susceptibility to infection and cancer (Holick and Chen, 2008;Lange et al, 2009). Recently, vitamin D insufficiency (defined as 25-hydroxy-vitamin D serum level of 20-29 ng/ml) has been proposed as a predictor of failure of treatment of chronic hepatitis C with PEG-IFNa and ribavirin (Abu Mouch et al, 2011;Petta et al, 2010). Moreover, severe vitamin D deficiency (defined by a 25-hydroxy-vitamin D serum level 520 ng/ml) is a common feature of chronic hepatitis C, even in the absence of advanced liver fibrosis (Lange et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, vitamin D deficiency was associated with several immunemediated diseases and increased susceptibility to infection and cancer (Holick and Chen, 2008;Lange et al, 2009). Recently, vitamin D insufficiency (defined as 25-hydroxy-vitamin D serum level of 20-29 ng/ml) has been proposed as a predictor of failure of treatment of chronic hepatitis C with PEG-IFNa and ribavirin (Abu Mouch et al, 2011;Petta et al, 2010). Moreover, severe vitamin D deficiency (defined by a 25-hydroxy-vitamin D serum level 520 ng/ml) is a common feature of chronic hepatitis C, even in the absence of advanced liver fibrosis (Lange et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro studies have shown that VD acts as an antiviral agent that inhibits hepatitis C virus (HCV) production in a human hepatoma cell line (DiCarlo et al, 2015). In patients with HCV that underwent OLT with subsequent recurrent HCV, high rates of sustained virologic response (SVR) were noted in patients receiving VDS (Abu-Mouch, Fireman, Jarchovsky, Zeina, & Assy, 2011;Bitetto et al, 2011;Iruzubieta et al, 2014).…”
Section: Sustained Virologic Responsementioning
confidence: 99%
“…Another predictor of response to PEGIFN/RBV therapy was found to be insulin resistance, which impairs response rates to PEG IFN/RBV therapy in HCV GT4 patients, and patients with Homeostasis Model Assessment for Insulin Resistance scores > 2 had lower SVR rates than those with scores < 2 (36% vs 72%) [147] . AbuMouch et al [148] found that adding vitaminD to the standard of care with PEGIFN/RBV therapy for HCVGT1 infected patients increases SVR rates from 42% to 82%. Esmat et al [149] reported that vitamin D supplementation, despite its role in other GTs, has no positive impact on treatment outcome in HCVGT4 patients where SVR was achieved in 51.2% in group 2, [who received the standard of care therapy (SOC .…”
Section: Background In Hcv Treatmentmentioning
confidence: 99%